Optimal Design and Analyses of T-shaped rotor Magnetorheological Brake. (October 2019) - Acharya, S; Saini, T R S; Kumar, H
Abstract: Magnetorheological (MR) brakes, belonging to the class of electromagnetic brakes, have a potential to replace conventional hydraulic brakes owing to reversible, rapidly controllable torque characteristics. In this study, T-shaped rotor MR brake was considered due to their higher braking torque capability and compactness compared to other configurations of brake. Optimal design of the brake was performed considering brake rotor radius, rotor thickness, flange length, casing thickness, coil height and coil width. Magnetostatic analyses were performed for different combinations of parameters of the brake dimensions to compute the magnetic flux density generated in the MR fluid region and the torque ratio and mass were calculated. The optimum dimensions of the brake were determined based on maximization of torque ratio and minimization of mass of the brake using multi-objective Genetic algorithm optimization technique. Further, magnetostatic analyses of the T-rotor brake with optimal dimensions were performed and torque characteristics were compared with those obtained for brake with simple disk rotor. It was concluded that T-rotor brake produces higher braking torque compared to simple disk rotor type MR brake for similar dimensions.